Respuesta :
Answer:
Step-by-step explanation:
Write the rule for h(f(x)).
h(f(x)) = 2x - 11
Write the rule for f(h(x)).
f(h(x)) = 2x - 4
The equation of the composite function is f(h(x)) = 2x-4.
What is Composite Function?
Function composition is an operation ∘ that takes two functions f and g, and produces a function h = g ∘ f such that h(x) = g. In this operation, the function g is applied to the result of applying the function f to x.
Here, f(x) = x - 7
h(x) = 2x + 3
Now, f(h(x)) = f ( 2x + 3)
= (2x+3)-7
= 2x + 3 -7
= 2x - 4
Thus, the equation of the composite function is f(h(x)) = 2x-4.
Learn more about Composite Function from:
https://brainly.com/question/20379727
#SPJ2